Pengaruh Sikap Agresif dan Sikap Antisosial terhadap Kecanduan Game Online Studi Kasus SMA Dharma Suci Jakarta Utara - Erwin Sugiyanto (Dhammavicaya : Jurnal Pengkajian Dhamma, 2023)
Adolescence is defined as a period of transitional development between childhood and adulthood which includes biological, cognitive, and socio-emotional changes. Adolescents have attitudes that tend to be more aggressive, emotionally unstable and unable to resist the impulse of lust. Teenagers have a great opportunity to become online game players due to online gaming activities which ultimately have an impact on the absence of socializing and communication activities with other people or social attitudes. In general, the purpose of this study was to determine the effect of aggressive and antisocial attitudes on online game addiction as a case study of SMA Dharma Suci. This study uses a quantitative approach with ex post facto methods and multiple linear regression analysis. The results of this study indicate that aggressive attitudes and antisocial attitudes have an effect on online game addiction in the case study of SMA Dharma Suci North Jakarta. The contribution of the influence of aggressive attitudes and antisocial attitudes towards online game addiction in the case study of SMA Dharma Suci North Jakarta students was 60.4%, while 39.6% was influenced by other variables not examined in this study.